2020
DOI: 10.3390/cells10010032
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Stretch of Either PNS or CNS Located Nerves Can Stimulate Neurite Outgrowth

Abstract: The central nervous system (CNS) does not recover from traumatic axonal injury, but the peripheral nervous system (PNS) does. We hypothesize that this fundamental difference in regenerative capacity may be based upon the absence of stimulatory mechanical forces in the CNS due to the protective rigidity of the vertebral column and skull. We developed a bioreactor to apply low-strain cyclic axonal stretch to adult rat dorsal root ganglia (DRG) connected to either the peripheral or central nerves in an explant mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…A tailored mechanical stretch (with a strain of 0.1-1% for cultured neurons and up to 10% for DRG explants) had positive effects on neurite outgrowth and pain modulation [27,30,36,37]. Higher levels of stretch had negative effects on neurons, such as impaired neurite regeneration and increased neuronal death [27,33,34,[36][37][38].…”
Section: Evidence From the Petri Dishmentioning
confidence: 99%
“…A tailored mechanical stretch (with a strain of 0.1-1% for cultured neurons and up to 10% for DRG explants) had positive effects on neurite outgrowth and pain modulation [27,30,36,37]. Higher levels of stretch had negative effects on neurons, such as impaired neurite regeneration and increased neuronal death [27,33,34,[36][37][38].…”
Section: Evidence From the Petri Dishmentioning
confidence: 99%
“…Moreover, stretch is also found to stimulate neurite growth of mature neurons. Ten percent cyclic stretch of nerve explants at 0.5 Hz enhanced neurite outgrowth of neurons from rat dorsal root ganglia ( Kampanis et al, 2020 ), and 10 pN of stretch could enhance axon growth and branching ( De Vincentiis et al, 2020 ). However, the conclusions of the amplitude of cyclic strain that can induce neurite outgrowth or neural differentiation are different from these studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has revealed that extracellular physical cues could transduce into intracellular force to control the intestinal organoid growth and development through Wnt/β-catenin signaling ( Li et al, 2020 ). Particularly, stretch could stimulate neuron growth ( Loverde and Pfister, 2015 ; Breau and Schneider-Maunoury, 2017 ), axon growth ( De Vincentiis et al, 2020 ), and neurite outgrowth ( Higgins et al, 2013 ; Kampanis et al, 2020 ). Moreover, we have reported that fluid shear stimulation could boost BMSC differentiation into endothelial cells and cardiomyocyte-like cells ( Bai et al, 2010 ; Huang et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also interesting to note that there are conflicting reports in terms of injury severity in mild stretch models [ 91 ], with some studies demonstrating beneficial effects of mild nerve stretch [ 92 , 93 ]. In contrast, severe axonal stretching induces critical and permanent deficits, including mitochondrial swelling and cell death [ 94 , 95 , 96 ].…”
Section: Axonal Stretch Injury Modelmentioning
confidence: 99%